Penyuluhan Kesehatan Tentang Hipertensi Pada Lansia di Dukuh Turi, Bambanglipuro, Bantul - Istichomah Istichomah (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2020)
ABSTRACT The purpose of health education in community is improve the health statuse, especially in the elderly who increase hypertension through a healthy lifestyle. The method is through health education about 1) identification of the lifestyle of the elderly in the local area, 2) prevention and management of hypertension in the elderly. The results of health education are well known that participants are very active in participating in this activity. Based on questionnaires given to participants before and after counseling, participants understanding of the knowledge of hypertension increased 80%, understanding of the prevention of hypertension increased 67%, understanding of curing of hypertension increased 68%, understanding of prevention and treatment of hypertension increased 76% . So that, Continuing Health education is very important to increased health live style. ABSTRACT The purpose of heath education in community is improve the health statuse, especially in the elderly who increase hypertension through a healthy lifestyle. The method is through health education about 1) identification of the lifestyle of the elderly in the local area, 2) prevention and management of hypertension in the elderly. The results of health education are well known that participants are very active in participating in this activity. Based on questionnaires given to participants before and after counseling, participants understanding of the knowledge of hypertension increased 80%, understanding of the prevention of hypertension increased 67%, understanding of curing of hypertension increased 68%, understanding of prevention and treatment of hypertension increased 76% . So that, Continuing Health education is very important to increased healthy live style.